Material Culture and Textiles: An Overview - Hood, Adrienne D. (Material Culture Review, 1990)
The majority of literature dealing with textile-related artifactual evidence has consisted of descriptive catalogues concerned primarily with identification of material but only minimally placing it into a broad historical context. Some recent studies have moved away from this approach, to look at the impact of cloth production and consumption on local social, economic and political realities. Scholars have examined such things as the use of fabrics to indicate wealth and status; the influence of British imperial policies on North American textile production; the differences between urban and rural production and use, and the impact of the migration of cultural traditions on the structure and output of textile-making. Despite the newer research, there remains a distinct polarity between the descriptive works on the one hand, focusing on objects, and those on the other that look at broader issues of textile use and production through an analysis of documentary evidence. This paper examines how we can begin to integrate the study of objects with more traditional historical research.RésuméLes textes consacrés aux documents archéo-logiques ayant rapport aux textiles sont, pour la plupart, des catalogues descriptifs où l'on s'attache principalement à décrire des arte-facts, sans s'attarder à les situer dans un contexte historique général. Certaines études publiées récemment s'écartent de ce modèle et tentent d'évaluer l'effet de la production et de la consommation de textiles sur les réalités sociales, économiques et politiques de cer-taines collectivités. Les chercheurs se sont ainsi penchés sur l'usage de certains tissus comme signes de richesse ou de rang social, l'influence des politiques impériales bri-tanniques sur la production textile en milieux urbain et rural, ainsi que les répercussions de la migration des traditions culturelles sur la structure et la productivité de l'activité textile. Malgré ces nouvelles recherches, on remarque encore une nette polarisation autour des travaux descriptifs centrés sur les objets eux-mêmes et de ceux où l'on analyse ces documents archéologiques dans une perspective plus vaste comme celle de l'utilisation et la production des textiles. Cet exposé examine la façon dont nous pourrions maintenant intégrer l'étude des objets à une démarche plus classique de recherche historique.